PENGETAHUAN AYAH SEBAGAI BREASTFEEDING FATHER TENTANG PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS TAMPAKSIRING I GIANYAR BALI 2014 - I Made Andika Adiguna; Wayan Citra Wulan Sucipta Dewi (Universitas Udayana, 2016)
KNOWLEDGE OF THE FATHER AS BREASTFEEDING FATHER IN EXCLUSIVE BREASTFEEDING PRACTICE IN PUSKESMAS TAMPAKSIRING I GIANYAR BALI 2014 Rate of exclusive breastfeeding in Indonesia is very low (42%), this rate is far from national target of 80%. The rate of exclusive breastfeeding rate in Puskesmas Tampaksiring I is not achieve national target. Many factor is affecting this result including knowledge of father as breast feeding father. Objective is to identify knowledge of the father as breastfeeding father in exclusive breastfeeding practice. This study was cross sectional. Conducted at the Puskesmas Tampaksiring I in August 2014. The subject was 59 father who had children aged 6 -12 months. Data collected with structured interview, the variables were knowledge of the father and practice of exclusive breastfeeding. The knowledge converted to a scoring system, than categorized into knowledge level. The result is proportion of exclusive breastfeeding is 61%. Knowledge of the respondent about: (1) breastmilk compare to other food (100%), (2) other food added at age 6 months (94,9%), (3) definition of exclusive breastfeeding (84,7%), (4) importance of it (84,7%), (5) breastmilk can protect baby from disease (66,1%), (6) long of exclusive breastfeeding is 6 months (64,7%), (7) breastmilk cannot be replaced by other food (55,9%), (8) understand colostrum (44,1%), and (9) its function (42,4%). Respondents with good knowledge level is 45,8%.